Transculturación, translingüismo y la novela "The Brief Wondrous Life of Oscar Wao" de Junot Díaz - Ingrid Petkova (Ksiegarnia Akademicka Publishing, 2020)
Transculturation, Translanguaging and Junot Díaz’s Novel, "The Brief Wondrous Life" of Oscar Wao